Ondokuz Mayıs Üniversitesi Müzik Eğitimi Anabilim Dalı Lisans Programı Flüt Dersinde Kullanılan Cecile Chaminade Op.107 Flüt Konçertino'sunun Uygulanabilirliğine Yönelik Teknik Önerilerin Belirlenmesi - Bulut, Seyhan (My University, 2015)
Bu çalışma romantik dönem flüt repertuvarına ait ve önemli eserlerden biri olarak tanınan Cecile Chaminade"nin op.107 numaralı konçertinosunu seslendirmek ve flüt eg itimi dersinde öğretmek isteyen akademisyenlere ışık tutması amacıyla yapılmıştır. Flüt dağarında evrensel bir yeri olan eserin daha net bir biçimde anlaşılıp yorumlanabilmesi ve flüt tekniği açısından yeni fikirler verebilmesi için hazırlanan çalışmada eserin uygulanabilirliğine yönelik teknik açıdan kolaylık sağlayacak birtakım çözüm önerileri sunulmakta, eser içinde yer alan önemli noktalar şekillerle açıklanmaktadır. Veri taraması yapılarak kaynaklardan elde edilen kişisel bilgilere kişisel deneyimlerin eklenmesiile eserin motif analizi yapılarak teknik zorluklara ilis kin ölçü kümeleri belirlenmistir. Belirlenen ölçülerin ve cümlelerin teknik zorluklarıyla ilişkili çözüm önerileri sunulmuştur. Eserin bilinçli bir şekilde icra edilebilmesi için bir klavuz niteliğinde hazırlanan bu çalışma flüt performans ve tekniğinin gelişimine olumlu katkılar sağlama amacı taşımaktadır

The improvement of the flute was completed by Theobald Boehm (1794-1881) in the 19th Century. Consequently, many pieces were composed for the new flute and it became indispensable as a solo and orchestral instrument. And for the same reason, flute became one of the important instruments, which is taught as a main instrument at the woodwinds and percussion departments of professional music education institutes in many countries around the world. Analysis of the 19th century flute works show their important contributions to the flute music. As a reflection of this fact, this research reveals Cecile Chaminade's (1857-1944) contribution to the romantic period flute literature with her work D major flute Concertino Op.107. This work, accepted as one of the leading flute works of the Romantic period has been a remarkable repertoire piece for flute education and concert programs since the very first time it was premiered. The questions of this study are determined as "What are the reflections of the Chaminade"s Concertino on today"s flute training at institutions providing professional music education at the undergraduate level?", "What are the technical difficulties of Chaminade"s Concertino?" and "How can a flute student overcome the tecnical difficulties in Chaminade"s Concertino?". In this context, literature review was made and attempts were made at accessing the whole literature to get information from the experts of the field who are aimed at identifying the flute works of the Romantic Period as well as the Chaminade Concertino. Also the work's motivic analysis was studied and the measure groups with technical difficulties have been identified. Technical ideas were formed with respect to personal experience. Also the composer of the concertino and flute instrument are described with respect to properties of the romantic period. Also the concertino"s remarkable contribute to the flute literature and to the Romantic Period Music are emphasized. This study is considered to be a useful resource for performers, scholars, educatiors and students who would like to perform or study this work. It is also convenient for scholars who undertake studies on flute literature of the romantic period. The technical sugesstions which are made in this study are expected to be quickly and efficiently understood and to be performed. The paper consists of four parts. The first part is an introduction in which the properties of the Paris School in the Late Romantic and significance of Chaminade and her concertino in the early 20th Century French School repertoire, which was formed of pieces that were mostly composed for instrumental competitions, were briefly explained. The Chaminade Flute Concertino was actually composed for competitions and it was also found convenient for final exam recital programs. For this reason it might be accepted as an educational piece, which aims to set the flute graduate level of the Paris School of the Early 1900"s. Also it is a sample piece that puts forward the properties related to syncopations, appogiaturas, accenturas and synchronization which form this schools" approach to virtuosity at that period. The ideas are formed according to those of Moyse, Hummel and Toff. The second part of the paper is about the characteristic properties of the concertino. It begins with a short explanation about "Concertino" genre. After that some ideas about the tonality of Chaminade"s work and its formal progression are summarized. The third and the longest part of the paper contains three sections. First two sections are about the form structure, titled as "the main theme" and "the bridge" in order. Here, besides the information about the formal outline, the sentences, periods and motives used throughout the piece are given. Also some renowned flute professionals" (such as Reedy, Galway, Hummel, Putnik, Horban, Carey and Schwoebel) answers to "how a particular passage should sound"; "where are the breathe-in moments"; "how should a particular passage be studied"; "what is the meaning of some rhythmic/melodic lines" are shared and explained in comparison with Debussy"s flute solo in L"apres midi du"n Faune. In addition, the development and alterations of the four appearances of the main theme are emphasized in this first section. The very short second section of the 3rd part is about the bridge between the first and second coming of the main theme. The last section of the third part is "the technical suggestions" which is meant to help the flute players to make it easier to practice and be able to play the concertino in shorter time. Technical suggestions are made especially for passages at bars 16, 17, 18, 23, 25, 26 and then the coming "piu animato agitato" section, followed by bars 73, 74, 83 which is emphasized as the most difficult bar of the piece and 94. After that, technical suggestions for "the cadence" section and the finale are explained in detail. The technical suggestions include some specific exercises for some specific bars. The paper concludes with the idea that Chaminade"s op.107 Concertino for Flute is a milestone in flute playing and a good choice of Romantic Flute Music practice for every student. It is stated that Cecile Chaminade"s op.107 flute concertino is extremely familiar work as a representative of the Romantic period flute literature in terms of musicality and interpretation. Chaminade made great contributions to the flute literatüre with this piece when compared with works of the important composers of the same period. The work is continuously included in both flute training and concert programs.
Determination of Technical Proposals for Cecile Chaminade's Flute ConcertinoOp.107 Which is Used in Flute Lessons at Undergraduate Education Program ofOndokuz Mayis University Music Education Department
Keywords: Eğitim; Eğitim Araştırmaları